Upaya Meningkatkan Kemampuan Berpikir Kritis dan Berpikir Kreatif Matematis Siswa SMA Melalui Model Pembelajaran Search, Solve, Create, and Share (SSCS) - Andrew Rolas Siagian (Departement of Mathematics Education, 2024)
The purpose of this study was to obtain a comprehensive picture of critical thinking skills and creative thinking skills obtained through Search, solve, create and share (SSCS) learning. This study was a quasi-experimental study. The experimental class was given SSCS learning and the control class was given conventional learning. The instruments used consisted of critical thinking skills tests and creative thinking skills tests. The statistical analysis used in this study was the Mann-Whitney test and two-way ANOVA. The results of the study showed that: (1) The increase in critical thinking skills of students who received learning with the SSCS model was higher than students who received learning with the conventional model in the high KAM and medium KAM categories. While in the low KAM category there was no difference in the increase in critical thinking skills between students who received SSCS learning and students who received conventional learning; (2) The increase in creative thinking skills of students who received learning with the SSCS model was higher than students who received learning with the conventional model in the medium KAM and low KAM categories. While in the high KAM category there was no difference in the increase in creative thinking skills between students who received SSCS learning and students who received conventional learning. (3) There is an interaction effect between the SSCS learning model and the conventional learning model with students' initial abilities (KAM) on increasing students' creative thinking abilities; (4) There is an interaction effect between the SSCS learning model and the conventional learning model with students' initial abilities (KAM) on increasing students' creative thinking abilities.